2022
DOI: 10.1093/bib/bbac403
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cell line-specific synergistic drug combinations through a relational graph convolutional network with attention mechanism

Abstract: Identifying synergistic drug combinations (SDCs) is a great challenge due to the combinatorial complexity and the fact that SDC is cell line specific. The existing computational methods either did not consider the cell line specificity of SDC, or did not perform well by building model for each cell line independently. In this paper, we present a novel encoder-decoder network named SDCNet for predicting cell line-specific SDCs. SDCNet learns common patterns across different cell lines as well as cell line-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…To present the performance of MGAE-DC predicting the synergy scores of drug combinations, which is a regression task, we compare it with four advanced methods including DeepSynergy [ 13 ], Matchmaker [ 14 ], PRODeepSyn [ 11 ], EC-DFR [ 20 ], HypergraphSynergy [ 32 ], TranSynergy [ 33 ] and SynPred [ 34 ]. Since some existing methods treat the prediction as a classification task, we also compare the performance of MGAE-DC with these methods including DTF [ 23 ], DeepDDS [ 16 ], Jiang’s method [ 29 ], SynPathy [ 35 ] and SDCNet [ 17 ]. For the classification task, the synergistic drug combinations are labeled as positive samples while the other combinations are treated as negative samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To present the performance of MGAE-DC predicting the synergy scores of drug combinations, which is a regression task, we compare it with four advanced methods including DeepSynergy [ 13 ], Matchmaker [ 14 ], PRODeepSyn [ 11 ], EC-DFR [ 20 ], HypergraphSynergy [ 32 ], TranSynergy [ 33 ] and SynPred [ 34 ]. Since some existing methods treat the prediction as a classification task, we also compare the performance of MGAE-DC with these methods including DTF [ 23 ], DeepDDS [ 16 ], Jiang’s method [ 29 ], SynPathy [ 35 ] and SDCNet [ 17 ]. For the classification task, the synergistic drug combinations are labeled as positive samples while the other combinations are treated as negative samples.…”
Section: Methodsmentioning
confidence: 99%
“…In this model, the drug chemical structures were treated as graphs, and the drug features were learned by a graph convolutional network (GCN) which encodes molecular topology information efficiently. Considering cell lines as different relations, the synergy data of drug combinations were modeled as a relational GCN (R-GCN) by Zhang et al’s SDCNet [ 17 ], where nodes are drugs, and edges are SDCs. Cell line-specific decoders were adopted to reconstruct the known SDCs, and predict new ones for each cell line, with the help of learned invariant features of drug combinations among the cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The biggest advantage of GCNN is its introduction of an optimized convolution parameter that extracts graph structure data features. This function is realized through a Laplace matrix in GCNN ( Zhang et al, 2022 ).…”
Section: Graph Convolutional Neural Networkmentioning
confidence: 99%
“…They are divided into two categories: , relational network-based methods and molecular structure-based methods. To predict drug synergy, relational network-based methods use heterogeneous knowledge graphs to represent relationships between different entities. Zhang and Tu , predicted drug synergy based on the drug and cell line embeddings of the synergistic combinations data through the graph embedding-based methods. Yue et al investigated drug–target heterogeneous network meta-pathways to explore molecular mechanisms of drug actions and forecast both the adverse and synergistic effects of drug combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al investigated drug–target heterogeneous network meta-pathways to explore molecular mechanisms of drug actions and forecast both the adverse and synergistic effects of drug combinations. Zhang et al considered the synergistic drug combination graphs of different cell lines as a relational graph and constructed a relational graph convolutional network to learn and fuse the representations of drugs on different cell lines for synergy prediction. Molecular structure-based methods explore drug synergy by using information about drugs’ chemical structures. At the same time it has been demonstrated that the pharmacological activity of drugs is primarily derived from their chemical substructures, , so that taking global structural information into account may result in erroneous predictions.…”
Section: Introductionmentioning
confidence: 99%